Implementation and Clinical Impact of a Guideline for Standardized, Evidence-Based Induction of Labor - Triebwasser, Jourdan E.; Louis, LeAnn; Bailey, Joanne M.; Mitchell-Solomon, Leah; Malone, Anita M.; Hamm, Rebecca F.; Moniz, Michelle H.; Stout, Molly J. (American Journal of Perinatology, 2024)
Objective This study aimed to assess the impact of implementation of an induction of labor (IOL) guideline on IOL length and utilization of evidence-based practices.Study Design We conducted a quality improvement project to increase utilization of three evidence-based IOL practices: combined agent ripening, vaginal misoprostol, and early amniotomy. Singletons with intact membranes and cervical dilation ≤2 cm admitted for IOL were included. Primary outcome was IOL length. Secondary outcomes included cesarean delivery and practice utilization. We compared preimplementation (PRE; November 1, 2021 through January 31, 2022) to postimplementation (POST; March 1, 2022 through April 30, 2022) with sensitivity analyses by self-reported race and ethnicity. Cox proportional hazards models and logistic regression were used to test the association between period and outcomes.Results Among 495 birthing people (PRE, n = 293; POST, n = 202), IOL length was shorter POST (22.0 vs. 18.3 h, p = 0.003), with faster time to delivery (adjusted hazard ratio [aHR] = 1.38, 95% CI: 1.15–1.66), more birthing people delivered within 24 hours (57 vs. 68.8%, adjusted odds ratio [aOR] = 1.90 [95% CI: 1.25–2.89]), and no difference in cesarean. Utilization of combined agent ripening (31.1 vs. 42.6%, p = 0.009), vaginal misoprostol (34.5 vs. 68.3%, p < 0.001), and early amniotomy (19.1 vs. 31.7%, p = 0.001) increased POST.Conclusion Implementation of an evidence-based IOL guideline is associated with shorter induction time. Additional implementation efforts to increase adoption of practices are needed to optimize outcomes after IOL.Key Points
Keywords: induction of labor; evidence-based practices; guideline; implementation; combined agent ripening; misoprostol; early amniotomy